An energetic composite formed of wrinkled rGO sheets wrapped around copper azide nanowires with higher electrostatic safety as a green primary explosive. Issue 51 (19th August 2020) - Liu, Xuwen; Hu, Yan; Li, Tingting; Ye, Yinghua; Shen, Ruiqi
Abstract : A green primary explosive with high energy density and electrostatic safety based on copper azide and rGO was designed. Abstract : A green primary explosive with high energy density and electrostatic safety was synthesized in this work. A precursor consisting of wrinkled reduced graphene oxide sheets wrapped around copper nanowires (CuNWs@rGO) was fabricated through a facile one-pot hydrothermal approach. The as-prepared precursor was deposited on a silicon wafer by electrophoretic deposition technology, which significantly reduced the safety risks of directly handling the powder sample in the azide reaction. Wrinkled rGO sheets wrapped around copper azide nanowires (CANWs@rGO) were prepared in situ by reaction of the precursor with HN3 gas. The initiation capability was tested by using it to detonate hexogen (RDX) against a lead plate with a thickness of 5 mm, and its detonation performance was found to be better than that of commercial diazodinitrophenol (DDNP). The electrostatic sensitivity of the CANWs@rGO composite was investigated, and the result shows that the discharge energy at 50% ( E 50% ) of CANWs@rGO was 0.96 mJ, which indicates that it has a much higher electrostatic safety than that of pure copper azide (0.05 mJ).